Fiscal Policy, Private Consumption, and Economic Growth among the Economic Community of West African States - Adelowokan, Oluwaseyi Adedayo (Universitas Muhammadiyah Yogyakarta, 2021)
This study examines the impact of fiscal policy and private consumption on economic growth among the Economic Community of West African States (ECOWAS) spanning from 1988 to 2017 using the Panel Pool Mean Group. The results depicted that the government’s recurrent expenditure for growth was inversely but significant to economic growth, while capital expenditure was positively and statistically significant to explain economic growth in Nigeria. It can be seen that capital expenditure is vital for economic growth. Besides, private consumption’s negative effect on economic growth was a disconnection between economic output and private consumption. The results further showed that tax revenues in ECOWAS countries had a positive and significant influence on economic growth. Therefore, the study recommends re-visit government policy(ies) channeling government spending to increase ECOWAS output rates and spur regional economic growth.